Operations Management / Producing Goods and Services - Waters Donald (Addison-Wesley, 1996)
This book successfully highlights the vital contribution that operations managers make to the long-term success of an organization. Introducing Operations Management, Planning the Product, Decisions about the Process, Planning and Scheduling Resources, Materials Management, Appendices, Index.